2022
DOI: 10.15244/pjoes/143911
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Temporal Evolution Pattern and Influencing Factors of Green Innovation Efficiency: Based on Provincial Panel Data of Chinese Industrial Enterprises

Abstract: Based on the panel data of 30 provinces in China from 2009 to 2017, the Super-SBM model with undesirable output is used to measure the green innovation efficiency (GIE) of Chinese industrial enterprises, and the Moran's I is used to analyze the spatial correlation. Then, spatialtemporal distribution characteristics are analyzed. Finally, the spatial panel model is used to examine the influencing factors of GIE. The results show that the GIE of Chinese industrial enterprises is at a low level, but it shows an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…According to Yang Dong and Chai Huimin (2015), "green technology innovation" is a kind of innovation that can realize energy saving and emission reduction, and reduce or even eliminate the negative impact on the environment by means of technology, process and product. Li Wanhong (2017) suggests that the principle of environmental protection is integrated into every innovation in the R&D process so as to minimize the impact on the environment.…”
Section: Concept Of Green Technology Innovationmentioning
confidence: 99%
“…According to Yang Dong and Chai Huimin (2015), "green technology innovation" is a kind of innovation that can realize energy saving and emission reduction, and reduce or even eliminate the negative impact on the environment by means of technology, process and product. Li Wanhong (2017) suggests that the principle of environmental protection is integrated into every innovation in the R&D process so as to minimize the impact on the environment.…”
Section: Concept Of Green Technology Innovationmentioning
confidence: 99%
“…In response to this problem, Tone constructed the network SBM model, a non-radial, non-angle efficiency measurement model based on slack variables, which can measure not only the overall efficiency value of the decision unit, but also the stage efficiency value, which is conducive to researchers to comprehensively analyze the technological innovation efficiency of the research object and make objective accurate judgment [18] . After a comprehensive comparison of technology innovation efficiency-related measurement models, the two-stage Super-efficiency Network SBM model (SBM model) [19] under CRS conditions is selected in this paper to measure the green technology innovation efficiency of industrial enterprises in Qinghai Province, and the specific formula is shown below. ISSN 2616-5902 Vol.…”
Section: Two-stage Super-nsbm Modelmentioning
confidence: 99%